Pengaruh Stres Kerja, Keterlibatan Kerja, Kepuasan Kerja Terhadap Kinerja Karyawan Pada PT. Corona Dwi Daya Balikpapan - Dyah Rini Prihastuty; Ratnaningsih Sri Yustini (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research discusses the influence of work stress, work involvement, and job satisfaction on employee performance at PT. CORONA DWI DAYA BALIKPAPAN. This research uses quantitative methods with a total of 50 employees as respondents. Sampling was taken using stratified random sampling. The application used to test this research was SPSS 18. Data analysis techniques used multiple linear regression analysis, validity test, reliability test, classical assumption test, hypothesis test, and multiple determinant analysis (R2). The results of this research show that the t-test carried out partially shows that the work stress variable has a negative and significant effect on employee performance, the work engagement variable has a positive and significant effect on employee performance, the job satisfaction variable has a positive and significant effect on employee performance. Regarding the F test, it shows that the variables Job Stress, Job Engagement, and Job Satisfaction simultaneously significantly affect Employee Performance at PT. CORONA DWI DAYA Balikpapan.